2005
DOI: 10.1021/jf050671m
|View full text |Cite
|
Sign up to set email alerts
|

Probing Anthocyanin Profiles in Purple Sweet Potato Cell Line (Ipomoea batatas L. Cv. Ayamurasaki) by High-Performance Liquid Chromatography and Electrospray Ionization Tandem Mass Spectrometry

Abstract: A purple line cell line (PL) generated from the storage root of purple-fleshed sweet potato (Ipomoea batatas L.) cv. Ayamurasaki produces a complex mixture of anthocyanins, and seven major anthocyanins have been isolated and identified to date. All these anthocyanins are exclusively cyanidin or peonidin 3-sophoroside-5-glucosides and their acylated derivatives. High-performance liquid chromatography (HPLC) coupled to photodiode array (PDA) detection and electrospray ionization tandem mass spectrometry (ESI-MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 31 publications
7
96
1
1
Order By: Relevance
“…This anthocyanin has been measured in both uncooked (Montilla et al, 2010) and cooked purple sweet potatoes (Truong et al, 2010) and was the most thermally stable anthocyanin associated with protection against a colorectal cancer model from intake of PFSP . This latter anthocyanin can be digested via deglycosylation to form cyanidin 3-p-hydroxy-benzoyl-sophoroside (m/z 731) (M (893)-162 for the loss of glucose) (Tian, Konczak, & Schwartz, 2005), which was detected in all five sections of the gut model with PM09.812 and in the V2-V5 vessels of PM09.960.…”
Section: Resultsmentioning
confidence: 99%
“…This anthocyanin has been measured in both uncooked (Montilla et al, 2010) and cooked purple sweet potatoes (Truong et al, 2010) and was the most thermally stable anthocyanin associated with protection against a colorectal cancer model from intake of PFSP . This latter anthocyanin can be digested via deglycosylation to form cyanidin 3-p-hydroxy-benzoyl-sophoroside (m/z 731) (M (893)-162 for the loss of glucose) (Tian, Konczak, & Schwartz, 2005), which was detected in all five sections of the gut model with PM09.812 and in the V2-V5 vessels of PM09.960.…”
Section: Resultsmentioning
confidence: 99%
“…The chromatographic conditions were optimised to generate a complete separation of all main peaks, which exhibited typical anthocyanin spectral profiles, with a maximum absorbance at 520-530 nm (Tian, Konczak, & Schwartz, 2005;Truong et al, 2010). The reference chromatographic fingerprint (Fig.…”
Section: Hplc Fingerprint Profiles Of Different Psp Cultivarsmentioning
confidence: 99%
“…Fan et al (2008) proved that the anthocyanins in purple sweet potato are mainly cyanidin and peonidin which are glycosylated with sugars. Tian et al (2005) indicated that the glycosylated anthocyanins are commonly mono-or di-acylated with caffeic, ferulic and hydroxybenzoic acids. This structure complication leads to a big challenge to the identification of PSPAs.…”
Section: Compositions Of Psp Extractmentioning
confidence: 99%